Spread through Air Spaces (STAS) in Solitary Pulmonary Metastases from Colorectal Cancer (CRC) - Haj Khalaf, Mohamed Anwar; Sirbu, Horia; Hartmann, Arndt; Agaimy, Abbas; Dudek, Wojciech; Higaze, Mostafa; Rieker, Ralf (The Thoracic and Cardiovascular Surgeon, 2022)
Background Spread through air spaces (STAS) is a recently described route of tumor invasion associated with poor prognosis in primary lung cancer. Aim of this study was to investigate the presence of STAS and to assess its prognostic significance in patients undergoing pulmonary metastasectomy (PM) for solitary metastases from colorectal cancer (CRC).Materials and Methods All 49 CRC patients (30 male and 19 female, median age 66 years) who underwent PM between January 2008 and December 2015 were retrospectively analyzed.Results STAS was identified in 26.5% (n = 13) of resected specimens. Location of pulmonary lesions (central vs. peripheral) was assessed based on the available computed tomography imaging (n = 47, 96%). STAS was detected in all five patients with central metastases (100%) versus 7 of 42 (17%) with peripheral metastases (p = 0.0001). Locoregional recurrence occurred in STAS-positive patients (n = 4 of 13 vs. n = 0 of 36), all STAS-negative patients remained recurrence-free (p = 0.003). Median number of alveoli with STAS involvement was four (range from 2 to 9). There was statistically positive relationship between the number of alveoli invaded with STAS and locoregional recurrence of metastases (p = 0.0001). The presence of STAS is not a factor affecting the 5-year overall survival rate (p = 0.6651).Conclusion We identified STAS as a frequent finding in resected CRC lung metastases and found insignificant association with outcome.
Keywords: metastases/metastasectomy; lung cancer; diagnosis; histology